Inflammatory and regenerative responses in salmonids following mechanical tissue damage and natural infection - Ingerslev, H.C.; Lunder, T.; Nielsen, M.E. (Fish & shellfish immunology, 2010)
Locale responses in muscle tissue against either a sterile tissue damage or infection were compared in salmonid fish in order to examine the inflammatory responses and regeneration of tissue. From higher vertebrates both damage and infection are known to cause inflammation since DAMPs released from injured cells as well as PAMPs from the surface of pathogens are immunogenic. To examine this in salmonid fishes, Atlantic salmon ( Salmo salar) were infected with Moritella viscosus, the causative agent of winter ulcer. Muscle tissue was sampled from infected fish at 4, 7 and 14 days post infection. Samples were obtained from site of lesions and from locations without clinical signs of disease and lesions. The tissue damage was performed in rainbow trout ( Oncorhynchus mykiss) by applying sterile needles to skin and muscle tissue to one side of the fish. Samples were taken 7, 14, 21, 28 and 42 days post injury from the injured side and non-injured site (internal control). From both infected and damaged fish, samples were subject to real-time RT-PCR for measuring the expression of IL-1β, IL-8, IL-10, Hsp70, iNOS, TGF-β, TLR-5m, TLR-9, TLR-22, TGF-β, MMP-2, CTGF, myostatin-1αβ and collagen-1α which are coding for immunological factors and tissue regeneration. Locale, inflammatory responses were seen as strong up-regulation of IL-1β and IL-8 in both groups of fish, but it was more pronounced in infected fish. Expression of the toll-like receptors showed induction of TLR-5m following infection, but TLR-9 and TLR-22 following damage. Further, in both studies the regenerative genes TGF-β, MMP-2, CTGF, myostatin-1αβ were induced, but showed different kinetics. Collagen-1α was only induced in infected fish, probably due to heavier tissue damage in these.